Electrolyte and Mineral Homeostasis After Optimizing Early Macronutrient Intakes in VLBW Infants on Parenteral Nutrition. Issue 4 (October 2015) - Senterre, Thibault; Abu Zahirah, Ibrahim; Pieltain, Catherine; de Halleux, Virginie; Rigo, Jacques
ABSTRACT: Objectives: The aim of the present study was to evaluate electrolyte and mineral homeostasis in very-low-birth-weight (VLBW) infants who received high protein and energy intakes with a unique standardized parenteral nutrition solution containing electrolytes and minerals from birth onward. Methods: Prospective cohort study in 102 infants with birth weight <1250 g. The evolution of plasma biochemical parameters was described during the first 2 weeks of life. Results: During the first 3 days of life, mean parenteral intakes were 51 ± 8 kcal · kg −1 · day −1 with 2.7 ± 0.4 g · kg −1 · day −1 of protein, 1.1 ± 0.2 mmol · kg −1 · day −1 of sodium and potassium, and 1.3 ± 0.2 mmol · kg −1 · day −1 of calcium and phosphorus. Afterwards, most nutritional intakes (parenteral and enteral) met growth requirements. No infant developed a hyperkalemia >7 mmol/L, and a hypernatremia >150 mmol/L occurred only in 15.7% of the infants. In contrast, hyponatremia <130 mmol/L and hypokalemia <3 mmol/L occurred in 30.4% and 8.8% of the infants, respectively. The initial neonatal metabolic acidosis rapidly resolved in most infants and only 2.0% developed a base deficit >10 mmol/L after day 3 of life. Early hypocalcemia <1.8 mmol/L occurred in 13.7% of the infants. In contrast, hypophosphatemia <1.6 mmol/L occurred in 37.3% and hypercalcemia >2.8 mmol/L occurred in 12.7% of the infants. Conclusions: Increasing early protein and energy intakes in VLBW infants in the first week of life improves electrolyte homeostasis. It also increases the phosphorus requirements with a calcium-to-phosphorus ratio ⩽1.0 (mmol/mmol) and the potassium and sodium requirements to avoid the development of a refeeding-like syndrome. These data suggest that the parenteral nutrition guidelines for VLBW infants for the first week of life need to be revised. Abstract : Supplemental Digital Content is available in the text